STUDY ON CONSUMER ACCEPTANCE OF AMPLANG FROM DIFFERENT FISH PROCESSED - Doni Mario; Dewita Buchari; Sumarto ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The purpose of this research was to determine the consumer acceptance level of amplang from. different fish processed. The method used in this research was experimental analysis with randomized designed non factorial, with different three of fish treatment (Pangasius hypophtalmus ;A1), (Clarias batracus ; A2), and (Oreochromis sp; A3) with triplicate in each treatment. The results showed that different fish the different fish treatment of amplang was significantly affect to consumer acceptance level. Amplang from different fish species treatment had value for A1 (83,44%), A2 (89,69%), and A3 (95,63%). Amplang wich was made from Oreochromis sp (A3) was the best treatment with characteristic ; white appearance, strongly scent, compact texture, and fishly in taste; water content 8.32%, fat content 14.96%, ash content 2.740% and protein content 10.89%.keywords : Amplang, consumer acceptance, different fish